2006
DOI: 10.1016/j.tate.2006.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Developing fundamental principles for teacher education programs and practices

Abstract: Traditional approaches to teacher education are increasingly critiqued for their limited relationship to student teachers' needs and for their meager impact on practice. Many pleas are heard for a radical new and effective pedagogy of teacher education in which theory and practice are linked effectively. Although various attempts to restructure teacher education have been published, no coherent body of knowledge exists about central principles underlying teacher education programs that are responsive to the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
457
1
83

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 735 publications
(598 citation statements)
references
References 31 publications
(27 reference statements)
9
457
1
83
Order By: Relevance
“…This finding corroborates Korthagen et al (2006) statement that pre-service teachers do not always adopt what they learn during their preparation programs. The third student teacher stayed on the same level for all three lesson study cycles.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding corroborates Korthagen et al (2006) statement that pre-service teachers do not always adopt what they learn during their preparation programs. The third student teacher stayed on the same level for all three lesson study cycles.…”
Section: Discussionsupporting
confidence: 88%
“…The linking of theory and practice is one of the crucial issues in teacher education and systematic, purposeful reflection is considered vital in this process (Dewey 1933;Korthagen et al 2006). Schön (1987) distinguishes between reflection-in-action and reflection-on-action.…”
Section: Reflection and Professional Noticingmentioning
confidence: 99%
“…The CPD programme required the collective participation of all teachers who taught in the same grade at the schools, and there were plenty of opportunities to engage in active learning sessions. The trainer provided the teachers with extensive feedback, because learning about teaching is enhanced when the approaches that are advocated in the CPD programme are modelled by the teacher educator who is delivering the CPD programme (Korthagen, Loughran, & Russell, 2006). A considerable part of the CPD programme consisted of video-based learning, since research has shown that the use of videos can yield positive effects on teachers' beliefs and on their interaction skills (Fukkink, Trienekens, & Kramer, 2011;Van Es & Sherin, 2010).…”
Section: Contextmentioning
confidence: 99%
“…There are warnings against a complete shift towards doing and performing rather than knowing and understanding -the danger of a model which focuses on practical experiences as if separate from the theoretical input. Korthagen (2006Korthagen ( :1021 refers to three aspects that haunt teacher education in the 21 st century: Firstly, the complaints from graduates, parents and politicians about the irrelevance of teacher preparation "for the reality of everyday practice in schools"; secondly, the body of research presenting evidence of a reality shock, followed by a "wash-out" effect experienced by new teachers; thirdly, there are new conceptions of teaching and learning such as constructivist views, situated knowledge and recognition of the importance of experience. To Korthagen's list, we can probably add the lack of recognition of the role of perceptual knowledge and metacognition.…”
Section: Patterns Of Change In a Teacher Education Curriculummentioning
confidence: 99%